Step
*
1
1
1
1
1
1
of Lemma
Legendre-rpolynomial
1. n : ℕ
2. ¬(n = 0 ∈ ℤ)
3. ¬(n = 1 ∈ ℤ)
4. a : ℕn - 1 ⟶ ℝ
5. b : ℕn ⟶ ℝ
6. x : ℝ
7. r(n) ≠ r0
8. (Σi≤n. λi.if (i =z 0) then (1 - n * a i)/n
             if i <z n - 1 then ((2 * n) - 1 * b (i - 1))/n - (n - 1 * a i)/n
             else ((2 * n) - 1 * b (i - 1))/n
             fi _i * x^i) ∈ ℝ
⊢ λi.if i ≤z n - 2
     then (r((2 * n) - 1) * if (i =z 0) then r0 else b (i - 1) fi /r(n)) - (r(n - 1) * (a i)/r(n))
     else (r((2 * n) - 1) * if (i =z 0) then r0 else b (i - 1) fi /r(n))
     fi [k] = λi.if (i =z 0) then (1 - n * a i)/n
                 if i <z n - 1 then ((2 * n) - 1 * b (i - 1))/n - (n - 1 * a i)/n
                 else ((2 * n) - 1 * b (i - 1))/n
                 fi [k] for k ∈ [0,n]
BY
{ ((D 0 THEN Reduce 0 THEN Auto) THEN RepUR ``so_apply`` 0 THEN AutoSplit) }
1
1. n : ℕ
2. ¬(n = 0 ∈ ℤ)
3. ¬(n = 1 ∈ ℤ)
4. a : ℕn - 1 ⟶ ℝ
5. b : ℕn ⟶ ℝ
6. x : ℝ
7. r(n) ≠ r0
8. (Σi≤n. λi.if (i =z 0) then (1 - n * a i)/n
             if i <z n - 1 then ((2 * n) - 1 * b (i - 1))/n - (n - 1 * a i)/n
             else ((2 * n) - 1 * b (i - 1))/n
             fi _i * x^i) ∈ ℝ
9. k : ℤ
10. 0 ≤ k
11. k ≤ n
12. k ≤ (n - 2)
⊢ ((r((2 * n) - 1) * if (k =z 0) then r0 else b (k - 1) fi /r(n)) - (r(n - 1) * (a k)/r(n)))
= if (k =z 0) then (1 - n * a k)/n else ((2 * n) - 1 * b (k - 1))/n - (n - 1 * a k)/n fi 
2
1. n : ℕ
2. ¬(n = 0 ∈ ℤ)
3. ¬(n = 1 ∈ ℤ)
4. a : ℕn - 1 ⟶ ℝ
5. b : ℕn ⟶ ℝ
6. x : ℝ
7. r(n) ≠ r0
8. (Σi≤n. λi.if (i =z 0) then (1 - n * a i)/n
             if i <z n - 1 then ((2 * n) - 1 * b (i - 1))/n - (n - 1 * a i)/n
             else ((2 * n) - 1 * b (i - 1))/n
             fi _i * x^i) ∈ ℝ
9. k : ℤ
10. ¬(k ≤ (n - 2))
11. 0 ≤ k
12. k ≤ n
⊢ (r((2 * n) - 1) * (b (k - 1))/r(n)) = ((2 * n) - 1 * b (k - 1))/n
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  \mneg{}(n  =  0)
3.  \mneg{}(n  =  1)
4.  a  :  \mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbR{}
5.  b  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbR{}
6.  x  :  \mBbbR{}
7.  r(n)  \mneq{}  r0
8.  (\mSigma{}i\mleq{}n.  \mlambda{}i.if  (i  =\msubz{}  0)  then  (1  -  n  *  a  i)/n
                          if  i  <z  n  -  1  then  ((2  *  n)  -  1  *  b  (i  -  1))/n  -  (n  -  1  *  a  i)/n
                          else  ((2  *  n)  -  1  *  b  (i  -  1))/n
                          fi  \_i  *  x\^{}i)  \mmember{}  \mBbbR{}
\mvdash{}  \mlambda{}i.if  i  \mleq{}z  n  -  2
          then  (r((2  *  n)  -  1)  *  if  (i  =\msubz{}  0)  then  r0  else  b  (i  -  1)  fi  /r(n))  -  (r(n  -  1)  *  (a  i)/r(n))
          else  (r((2  *  n)  -  1)  *  if  (i  =\msubz{}  0)  then  r0  else  b  (i  -  1)  fi  /r(n))
          fi  [k]  =  \mlambda{}i.if  (i  =\msubz{}  0)  then  (1  -  n  *  a  i)/n
                                  if  i  <z  n  -  1  then  ((2  *  n)  -  1  *  b  (i  -  1))/n  -  (n  -  1  *  a  i)/n
                                  else  ((2  *  n)  -  1  *  b  (i  -  1))/n
                                  fi  [k]  for  k  \mmember{}  [0,n]
By
Latex:
((D  0  THEN  Reduce  0  THEN  Auto)  THEN  RepUR  ``so\_apply``  0  THEN  AutoSplit)
Home
Index